Students’ Perceptions of Hybrid Learning in The Face-To-Face Meeting System (PTM) Limited to Science Lesson at The MTs Level - Paramitha, Silvia Melinda; Nurul H., Lisdityanti; Zahroh Dinafil A, Farda; Tasyana W.F., Putri; Indayati, Tatik; Lastutik, Mudji; Utami, Sri; Maromi, Lailul (Indonesian Journal of Science Learning (IJSL), 2021)
This study aims to determine students' perceptions of learning Hybrid Learning in the Limited PTM System in Science Subjects Class IX at the SMP/MTs level. The research method uses descriptive qualitative methods. The data in the study were in the form of a questionnaire with 14 questions to students. The data analysis technique in this qualitative research is using data reduction, data presentation, and conclusions. One of the advantages of implementing Hybrid learning is being able to improve students' cognitive learning outcomes. However, in limited PTM the problem faced by students is limited student social interaction, students have difficulty understanding the material. So, among the weaknesses in limited PTM it is assumed that Hybrid Learning is able to overcome problems that occur when PTM is limited. So, it is important to do this research. The results of this study namely students' perceptions of Hybrid Learning learning that Hybrid Learning makes it easier for students to understand the material, students feel happy when learning Hybrid Learning because they can communicate directly both with teachers and with friends. So, it can be concluded that students' perceptions of Hybrid Learning give a positive response.